2021
DOI: 10.1039/d1cp02426d
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of Pd-catalysed alkoxycarbonylation of alkenes and alkynes

Abstract: This perspective highlights the computational modeling of alkene and alkyne alkoxycarbonylation at palladium catalysts. We cover studies on Pd–catalysed alkoxycarbonylation of alkenes with bidentate diphosphine ligands, which reveal a hydride...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…The η 3 -allyl complexes tend to be stable thermodynamic sinks on the PES and thus require significant activation for further reaction. [53][54][55] Here, we used two equivalents of explicit iPrOH to reduce the two double bonds. Slippage from the η 3 -allyl bonding mode to a η 1 -allyl bonding mode with a Ru-C sigma bond (with carbon#11) helps create room for the incoming solvent molecules forming 6 (ΔG 56 = 15.4 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The η 3 -allyl complexes tend to be stable thermodynamic sinks on the PES and thus require significant activation for further reaction. [53][54][55] Here, we used two equivalents of explicit iPrOH to reduce the two double bonds. Slippage from the η 3 -allyl bonding mode to a η 1 -allyl bonding mode with a Ru-C sigma bond (with carbon#11) helps create room for the incoming solvent molecules forming 6 (ΔG 56 = 15.4 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…91 This level has performed very well in a number of studies from our group. [52][53][54][55][56][57]…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies for the Pd-catalysed alkyne alkoxycarbonylation with P,N-chelating ligands revealed that an in situ base mechanism is operating. [14] As a representative example, Beller and coworkers reported palladium complex with two hemilabile P,Nligands for the alkoxycarbonylation of internal olefins. [15] The computational studies for this reaction have been reported by Tian [16] and our groups.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies by Bühl et al using DFT methods on alkyne alkoxycarbonylations with Pd catalysts incorporating hemilabile (Ph 2 PIJ2-Py)) ligands did unravel the elementary steps of the catalytic cycle. [36][37][38] Proton shuttling by the pyridyl groups in the initiation and termination steps have been found to be crucial in this mechanism. In the initiation step, the pyridyl group functions first as an in situ base and when protonated as an in situ acid, which protonates the coordinated alkyne followed by CO insertion.…”
Section: Introductionmentioning
confidence: 99%